2017
DOI: 10.3892/ijo.2017.4223
|View full text |Cite
|
Sign up to set email alerts
|

Role of nestin expression in angiogenesis and breast cancer progression

Abstract: Nestin is an intermediate filament protein and a stem cell marker expressed in several tumours. There is growing evidence of an association between the expression level of nestin and the pathogenesis of triple-negative breast cancer (TNBC). Nestin is also expressed in newly forming tumour vessels and is a valuable marker of ongoing angiogenesis. In this study, we aimed to evaluate the prognostic value of nestin expression in breast tumour cells and to determine whether this expression influences angiogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…Nestin might participate in neovascularization through cytoskeletal changes promoted by the interaction between cancer cells with stem cell properties and endothelial cells lining blood vessels in the tumor stroma. Nowak et al reported that Nestin expression in endothelial cells lining newly formed breast tumor-associated blood vessels was shown to be associated with the triple-negative subtype, lymph node metastases and shorter overall survival [17, 20]. Nestin contributes to activation of the EMT pathway by regulating the Wnt/β-catenin pathway [21] and may therefore play a role not only in the regulation of mitosis, but in tumor invasiveness [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nestin might participate in neovascularization through cytoskeletal changes promoted by the interaction between cancer cells with stem cell properties and endothelial cells lining blood vessels in the tumor stroma. Nowak et al reported that Nestin expression in endothelial cells lining newly formed breast tumor-associated blood vessels was shown to be associated with the triple-negative subtype, lymph node metastases and shorter overall survival [17, 20]. Nestin contributes to activation of the EMT pathway by regulating the Wnt/β-catenin pathway [21] and may therefore play a role not only in the regulation of mitosis, but in tumor invasiveness [18].…”
Section: Introductionmentioning
confidence: 99%
“…As there are no unambiguous results, there is a need to search for more sensitive markers for the evaluation of angiogenesis in CRC. Taking into account the results of previous studies (18,19), we suggest nestin as a new biomarker for angiogenesis assessment in patients with CRC.…”
Section: Discussionmentioning
confidence: 74%
“…Nestin, a protein of the intermediate filaments of the cytoskeleton, appears to be more specific marker for newly formed blood vessels (17)(18)(19). Initially, nestin expression was reported in neuroepithelial stem cells, but further studies revealed its presence in many other progenitor cells i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high number of nestinexpressing cases (14/16) among the TNBCs and the lack of expression reported in luminal (0/16) and HER2-positive (0/16) tumours suggested that nestin may be an important marker of BC differentiation. Further studies confirmed the clinical implications of nestin expression in TNBC and basallike tumours (34,55,(90)(91)(92)(93)(94)(95)(96)(97). Parry et al (90), in an IHC study of 245 human invasive BC cases, demonstrated that nestin expression in tumour cells was predominantly observed in basal-like tumours, as defined by the IHC panel proposed by Nielsen et al (23).…”
Section: Nestin As a Marker Of Basal-like Bcmentioning
confidence: 71%